Cash Flow Report RT 05/RW 22 Jakasampurna Village, Bekasi West for the 2020 Period - Rini Widyani, Azizah (Indonesian Operations Research Association (IORA), 2020)
The importance of the cash flow statement to see changes in net assets is sometimes still not realized by institutions or small organizations. For example, residents of RT 05/RW 22 Jakasampurna Village, West Bekasi. In this paper, a cash flow report for RT 05/RW 22 Jakasampurna Village, West Bekasi will be prepared. With the aim of presenting valid information related to cash disbursements and receipts in the 2020 period. The method chosen is the preparation of cash flow reports directly with data analysis using descriptive methods. The results of the analysis show that the final amount of cash for the 2020 period has increased from the 2019 period with a ratio of 1,207. This means that the value of their current assets includes at least the amount of their short-term liabilities.